Evolving Federal Education Policy: A Comparative Analysis of No Child Left Behind Act, Race to the Top, and Every Student Succeed Act - Dahal, Bhushan (KIC International Journal of Social Science and Management, 2024)
Federal education policy in the United States has evolved over the past two decades, reflecting shifting priorities in accountability, equity, and federal-state relations. This paper provides a comparative analysis of three significant federal education policies: the No Child Left Behind Act (NCLB), Race to the Top (RTTT), and Every Student Succeeds Act (ESSA). Using McDonnell and Elmore's (1987) policy instrument framework, this study examines each policy's mechanisms—ranging from mandates and inducements to capacity- building and system change— to drive educational reform. It further explores substantive areas of reform, including standardized testing, teacher accountability, curriculum standards, and funding strategies. The analysis highlights how NCLB's rigid accountability measures gave way to RTTT's competitive grant-based incentives and ESSA's more decentralized, flexible approach to state-led reforms. While these policies share the goal of improving K-12 education and addressing educational disparities, they differ in balancing federal oversight with state autonomy. This study underscores the complexities of federal education policymaking, illustrating the ongoing challenges in achieving sustainable and equitable education reforms. The findings contribute to policy discourse by identifying lessons from past reforms that can inform future education policy development.